PROFIL UMK, PERMASALAHAN DAN UPAYA PEMBERDAYAANNYA - Risnawati, Naniek (Coopetition : Jurnal Ilmiah Manajemen, 2018)
Micro Small Enterprises (MSEs) have an important role in the national economy. The roles of this sector include in various work, sources of income, materials services to meet the needs and means to develop human resources through entrepreneurship practices. The number of MSEs in Sumedang District has continued to increase. Based on data from the Cooperative Office of Micro Small and Medium Enterprises, the number of MSMEs in Sumedang Regency in 2013 reached 6,872 business units. This increase in MSMEs contributes greatly to the Economic Growth Rate in Sumedang Regency which currently reaches 4.69%. However, UMK still has many weaknesses in running its business. Therefore, in the empowerment of MSEs here needs a more comprehensive and appropriate planning that is able to facilitate MSEs in solving the problems it faces. This sector can survive and grow, can play a bigger role in the regional climate. Keywords: Micro Small Business, Problems, Empowerment